Microwave-assisted generation and reactivity of aza- and diazafulvenium methides: heterocycles via pericyclic reactions - Soares, Maria I. L. (2008)
Azafulvenium methides and diazafulvenium methides have been generated under microwave irradiation from 2,2-dioxo-1H,3H-pyrrolo[1,2-c]thiazoles and 2,2-dioxo-1H,3H-pyrazolo[1,5-c]thiazoles, respectively. Pericyclic reactions of these 1,7-dipole intermediates, namely, sigmatropic [1,8]H shifts, 1,7-electrocyclization or [8[pi]+2[pi]] cycloaddition led to the synthesis of a range of pyrrole and pyrazole derivatives. The first evidence for the azafulvenium methides by intermolecular trapping via [8[pi]+2[pi]] cycloaddition is reported.